On the Risk-Return Trade-Off in the Valuation of Assets - Adler, Michael (Journal of Financial and Quantitative Analysis, 1969)
This article has two goals. The first is to contrast two widely used definitions of risk aversion. The second is to establish the feasibility of plunging behavior, in the sense that a possibly large number of risk averse investors will not be diversifiers.